Tuberculosis paru pada anak di Salatiga: pengaruh kondisi rumah dan pendapatan keluarga - Namira Wadjir Sangadji; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Children with pulmonary tuberculosis in Salatiga: effect of housing condition and family income PurposeThis study aimed to analyze the social and environmental determinants associated with cases of childhood tuberculosis in the city of Salatiga 2015-2016.MethodThis study was a case control involving 130 children. Cases were children aged ≤15 years who were diagnosed tubercuosis by a doctor's examination based on the Indonesian pediatric association scoring system. Controls were children aged ≤ 15 years who were not had tuberculosis by a doctor's examination based on the Indonesian pediatric association scoring system. Data were collected through structured interviews and direct measurement of ventilation area, room, humidity and home lighting and coordinate measurements with global positioning system to determine the position of tuberculosis case point. ResultsThe pattern of pulmonary tuberculosis cases in children was spread over densely populated areas. Room density was the biggest risk factor in the incidence of childhood tuberculosis in Salatiga. A social condition that affected pulmonary tuberculosis the most was family income.ConclusionActive case finding is needed in low socioeconomic groups and densely populated areas. Health promotion of healthy house requirements needs to be given to the community.